2008
DOI: 10.1007/978-3-540-88458-3_98
|View full text |Cite
|
Sign up to set email alerts
|

A Fast and Fully Automatic Ear Recognition Approach Based on 3D Local Surface Features

Abstract: Abstract. Sensitivity of global features to pose, illumination and scale variations encouraged researchers to use local features for object representation and recognition. Availability of 3D scanners also made the use of 3D data (which is less affected by such variations compared to its 2D counterpart) very popular in computer vision applications. In this paper, an approach is proposed for human ear recognition based on robust 3D local features. The features are constructed on distinctive locations in the 3D e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…[22] and [20] utilized face recognition to provide continuous and transparent authentication for desktops and mobile devices respectively. [23] proposed a fast and fully automatic ear recognition approach based on 3D local surface features for generic usage; while [24] investigated an implicit authentication technique based upon ear shapes during a call session on smartphones. By using touch screens, [25] and [26] demonstrated that fingerprint identification can be utilized to provide transparent and continuous protection for mobile devices.…”
Section: Physiological Transparent Biometricsmentioning
confidence: 99%
“…[22] and [20] utilized face recognition to provide continuous and transparent authentication for desktops and mobile devices respectively. [23] proposed a fast and fully automatic ear recognition approach based on 3D local surface features for generic usage; while [24] investigated an implicit authentication technique based upon ear shapes during a call session on smartphones. By using touch screens, [25] and [26] demonstrated that fingerprint identification can be utilized to provide transparent and continuous protection for mobile devices.…”
Section: Physiological Transparent Biometricsmentioning
confidence: 99%
“…Instead of using traditional features like curvatures, we adopted a local PCA-based feature introduced by Islam et al in [20]. The extracted 3D-ear could be represented as a point…”
Section: Ear Feature Extractionmentioning
confidence: 99%
“…According to [20], δ i can actually represent the difference of first two principal axes at a local region around p i and it will be zero if the point cloud L i is planar or spherical. By calculating {δ i } for all the points {p i }, we can obtain a feature map.…”
Section: Ear Feature Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 shows the anatomy of the human entire ear. Thus, it is considered to be a suitable alternative method or complement to the face for current human identification (Ossowskia et al, 2013;Hurley et al, 2007;Islam et al, 2008a). A biometric system is a pattern recognition system that establishes the authenticity of a specific physiological or behavioral characteristic possessed by a user.…”
Section: Introductionmentioning
confidence: 99%